Tatak Pilipino [episode no. 52] ([Quezon City ABS-CBN], 1991)
A unique display of Pilipino ways and style.
Forenza MTV (10 min.) --U.F.O. series-Lemuria (15 min.) -- El Filibusterismo on stage play (15 min.) --Nayong Pilipino (15 min.) -- Historical rap calendar events of December (5 min.).
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Unidentified flying objects; Political plays, Filipino; Philippines -- History; Theater art; Geography